Pengembangan Sistem Manajemen Keuangan (Studi Kasus: CV Gumcode Indonesia) - Kurnia Rizky Triantoko; Djoko Pramono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
CV Gumcode Indonesia is a service company which develop a software, that initiated from startup in 2013 and became CV in 2018. The case that happened in 2017 was a problem in managing the company's asset data because of the incomplete SOP of financial management . Although the losses are relative small, call it less than 1 digit nominal, it has possibility to be happened again even worse if preventive action are not taken. This leads the company to plan to use the information technology likely a software, which can accommodate financial management activities in according of the created SOP. To be able to create the system, it is necessary to do software engineering with the waterfall method, because it has advantage when user needs are stable and do not change as like as the current condition of the CV Gumcode Indonesia. In addition of using waterfall method, the modeling method are using Unified Modeling Language (UML) and Business Process Model and Notation (BPMN) to support the software engineering cycle. The activity of business process produces 3 business processes (to-be). While the analysis and design activities using UML produce 14 use case diagrams, 4 controller classes, 7 model classes, 17 sequence diagrams and 13 tables in the database. In testing phase, it is using validation testing that states most of needs or features show valid output, and compatibility testing shows there is 1 critical issue on https security for browsers Firefox and Chrome, and major issues in CSS definition for browser IE and Safari.